Initial clinical experience with high-pitch dual-source CT as a rapid technique for thoraco-abdominal evaluation in awake infants and young children. Issue 12 (December 2019) - Tabari, A.; Patino, M.; Westra, S.J.; Shailam, R.; Sagar, P.; Sahani, D.V.; Nimkin, K.; Gee, M.S.
Abstract : AIM: To evaluate dual-source high-pitch computed tomography (HPCT) imaging of the chest and abdomen as a rapid scanning technique to obtain diagnostic-quality imaging evaluation of infants and young children without sedation. MATERIALS AND METHODS: Fifty-three paediatric patients (age 24.1±2 months) who underwent chest or abdomen HPCT (≥1.5) and standard pitch CT (SPCT, <1.5) on a dual-source 128-row multidetector CT system were included in the study. Image quality assessment was performed by two paediatric radiologists for diagnostic confidence, image artefacts, and image noise. Objective image noise was measured. RESULTS: Most of the CT examinations were performed in children who were >1 year old ( n= 15 and n= 20) followed by ≤1 year old ( n= 8 and n= 10) in SPCT and HPCT, respectively. The mean radiation dose (SSDE) from HPCT was 1.96±1 mGy compared to 2.2±1 mGy for SPCT ( p =0.3). No major artefacts were reported and overall image quality of all HPCT examinations was acceptable diagnostically. In addition, objective image noise values were not significantly different between HPCT compared with SPCT (11±3 versus 11±5, p =0.7). CONCLUSION: Ultra-fast, HPCT can be performed without the need for sedation as a potential alternative to anaesthetised magnetic resonance imaging in infants and young children. Highlights: High-pitch DSCT protocols enable significant decrease in mean scan time in pediatrics. High-pitch DSCT provides excellent image quality using free-breathing technique. Objective noise was 30% lower in HP chest CT compared to SP chest CT (P=0.7). Mean CNR was 20% lower in SP abdomen CT compared to HPCT (P=0.1). No significant difference in SSDE between high-pitch and standard-pitch studies (P=0.3).